Global and Comparative Proteome Signatures in the Lens Capsule, Trabecular Meshwork, and Iris of Patients With Pseudoexfoliation Glaucoma - Sahay, Prity; Chakraborty, Munmun; Rao, Aparna (Frontiers in Molecular Biosciences, 2022)
Pseudoexfoliation (PXF) is characterized by the accumulation of exfoliative material in the eye and high rates of blindness, if left untreated. Pseudoexfoliation glaucoma (PXG) is generally diagnosed too late due to its asymptomatic nature, necessitating the development of new effective screening tools for the early diagnosis of the disease. Thus, the increasing prevalence of this disease due to an aging population has necessitated the identification of suitable biomarkers for the early detection of the disease or detection of the onset of glaucoma in eyes with PXF. We applied a proteomics strategy based on a high-throughput screening method for the determination of proteins involving PXF and PXG pathogenesis. Lens capsule (LC), iris, and trabecular meshwork (TM) samples with PXF and PXG were taken by surgical trabeculectomy and controls samples were taken from donor corneal buttons obtained from the institutional eye bank to characterize the proteome profile. Peptides from LC were analyzed using liquid chromatography with tandem mass spectrometry (LC-MS/MS). The protein of interest and cytokines/chemokines profiles were verified using immunohistochemistry and bio-plex kit assay, respectively. There was a total of 1433 proteins identified in human LC, of which 27 proteins were overexpressed and 8 proteins were under-expressed in PXG compared with PXF. Overexpressed proteins such as fibromodulin, decorin, lysyl oxidase homolog 1, collagen alpha-1(I) chain, collagen alpha-3(VI) chain, and biglycan were the major components of the extracellular matrix (ECM) proteins involved in cell-matrix interactions or ECM proteoglycans, assembly and crosslinking of collagen fibrils. The ECM composition and homeostasis are altered in glaucoma; thus, quantitative proteomics is a method to discover molecular markers in the eye. Monitoring of these events can help evaluate disease progression in future studies.